Fingerprint Comparison between Siblings and Their Parents Using Ridge Characteristics - K Swarnaambigaa,; Ms Keerthi S, (International Journal of Scientific Research in Science and Technology, 2025)
In modern times, fingerprint analysis is considered the most important aspect in forensic science practices and even personal identification. The contours that we have on our fingertips are used to form ridges, and fingerprint patterns are unique and lasting in nature. These patterns are called dermatoglyphics. This analysis proposes to look into the captivating world of fingerprint ridge features within two-child families focusing on youngest and oldest siblings. The most prominent aims of this investigation are: figure out how many distinct fingerprints there are within one family; check whether children’s fingerprints look like their parents'; analyse similarities between siblings in order to capture ridge features within a family. This research hopes to demonstrate familial relationships which control the development of dermal ridge patterns by systematically observing the youngest and oldest children’s fingerprint patterns with those of their parents using standard fingerprint pattern comparison methods. This study will focus on analysing the details of fingerprint minutiae with a specialized accent on uniqueness within familial relationships using NIST Fingerprint Registration and Comparison Tool (NFRaCT) and SPSS. The objective is to analyse the fingerprints of siblings and parents in order to evaluate the degree of resemblance and difference of ridge patterns within a family.
Keywords: fingerprint comparison; hereditary; ridge characteristics; similarities